Implicit Meanings of Social Issues in The Animated Series Freej: An Umberto Eco Semiotic Analysis: Al-Ma'ani al-Dimniyyah li al-Qadaya al-Ijtima'iyyah fi al-Musalsal al-Kartuni Freej: Dirasah Simiyaiyyah 'inda Umberto Eco - Nisaul Kamila; Zulkhairi Sofyan; Nurul Azmi (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study investigates the implicit meanings of social issues in the animated series Freej through the semiotic framework of Umberto Eco. Previous studies on Freej have primarily focused on cultural representation, identity construction, and the preservation of Emirati traditions, while limited attention has been given to the processes through which social meanings are implicitly produced and interpreted. Addressing this gap, the present study examines how social criticism is constructed through Eco’s typology of sign production. Employing a qualitative semiotic approach, the study analyzes five purposively selected episodes from Season 1 of Freej, chosen for their representation of tensions between tradition and modernity in contemporary Emirati society. The findings reveal that issues of modernization, cultural marginalization, and identity negotiation are communicated through visual composition, spatial organization, performative contrast, and linguistic interaction. These meanings emerge through the semiotic processes of recognition, ostension, replica, and invention, which enable viewers to actively interpret the social messages embedded in the narrative. The study demonstrates that Freej functions as an open text that conveys social criticism implicitly rather than through direct verbal expression. Theoretically, this research extends the application of Eco’s typology of sign production to animated media and contributes to the understanding of how implicit social meanings are generated through audience-text cooperation. Practically, the findings highlight the potential of animation as a medium for social reflection, cultural awareness, and social critique in contemporary society. تهدف هذه الدراسة إلى الكشف عن المعاني الضمنية للقضايا الاجتماعية في المسلسل الكرتوني فريج (Freej) من خلال الإطار السيميائي لأومبرتو إيكو. وقد ركزت الدراسات السابقة حول فريج بصورة أساسية على التمثيلات الثقافية، وبناء الهوية، والمحافظة على التراث الإماراتي، في حين لم تحظَ عمليات إنتاج الدلالات الاجتماعية الضمنية وتأويلها باهتمام كافٍ. وانطلاقًا من هذه الفجوة البحثية، تسعى الدراسة الحالية إلى تحليل كيفية بناء النقد الاجتماعي من خلال أنماط إنتاج العلامة عند أومبرتو إيكو. وتعتمد الدراسة المنهج السيميائي الكيفي من خلال تحليل خمس حلقات مختارة قصدياً من الموسم الأول لمسلسل فريج، وذلك بناءً على تمثيلها لحالة التوتر بين التقاليد والحداثة في المجتمع الإماراتي المعاصر. وتكشف النتائج أن قضايا التحديث، والتهميش الثقافي، والتفاوض الهوياتي تُنقل عبر التكوين البصري، والتنظيم المكاني، والتقابل الأدائي، والتفاعل اللغوي. وتنبثق هذه المعاني من خلال العمليات السيميائية المتمثلة في التعرّف (Recognition)، والإشارة (Ostension)، والاستنساخ (Replica)، والابتكار (Invention)، مما يتيح للمشاهد المشاركة الفاعلة في تأويل الرسائل الاجتماعية المتضمنة في السرد. وتبين الدراسة أن فريج يعمل بوصفه نصًا مفتوحًا ينقل النقد الاجتماعي بصورة ضمنية بدلاً من التعبير اللفظي المباشر. وعلى المستوى النظري، توسع هذه الدراسة نطاق تطبيق أنماط إنتاج العلامة لدى أومبرتو إيكو في مجال الوسائط المتحركة، وتسهم في تعميق فهم كيفية إنتاج المعاني الاجتماعية الضمنية من خلال التفاعل التعاوني بين النص والمتلقي. أما على المستوى العملي، فتبرز نتائج الدراسة إمكانات الرسوم المتحركة بوصفها وسيلة للتأمل الاجتماعي، وتعزيز الوعي الثقافي، وإيصال النقد الاجتماعي في المجتمعات المعاصرة. Penelitian ini mengkaji makna-makna implisit dari isu-isu sosial dalam serial animasi Freej melalui kerangka semiotika Umberto Eco. Penelitian-penelitian sebelumnya tentang Freej umumnya berfokus pada representasi budaya, konstruksi identitas, dan pelestarian tradisi Emirat, sementara perhatian terhadap proses pembentukan dan penafsiran makna sosial secara implisit masih terbatas. Untuk mengisi kesenjangan tersebut, penelitian ini menganalisis bagaimana kritik sosial dibangun melalui tipologi produksi tanda yang dikemukakan oleh Umberto Eco. Penelitian ini menggunakan pendekatan semiotika kualitatif dengan menganalisis lima episode terpilih dari musim pertama Freej yang dipilih secara purposif berdasarkan representasinya terhadap ketegangan antara tradisi dan modernitas dalam masyarakat Emirat kontemporer. Hasil penelitian menunjukkan bahwa isu-isu modernisasi, marginalisasi budaya, dan negosiasi identitas dikomunikasikan melalui komposisi visual, pengorganisasian ruang, kontras performatif, dan interaksi linguistik. Makna-makna tersebut muncul melalui proses semiotik berupa pengenalan (recognition), penunjukan (ostension), replika (replica), dan invensi (invention), yang memungkinkan penonton secara aktif menafsirkan pesan-pesan sosial yang terkandung dalam narasi. Penelitian ini menunjukkan bahwa Freej berfungsi sebagai teks terbuka yang menyampaikan kritik sosial secara implisit, bukan melalui ekspresi verbal yang langsung. Secara teoretis, penelitian ini memperluas penerapan tipologi produksi tanda Umberto Eco pada media animasi serta berkontribusi pada pemahaman mengenai bagaimana makna sosial implisit dihasilkan melalui kerja sama antara teks dan audiens. Secara praktis, temuan penelitian ini menegaskan potensi animasi sebagai media refleksi sosial, peningkatan kesadaran budaya, dan penyampaian kritik sosial dalam masyarakat kontemporer.